Evaluation of the synergistic application of bone marrow aspirate concentrate and platelet-rich plasma therapy in women experiencing premature ovarian failure and poor ovarian reserve: a case series - Vyjayanthi, Srinivasan; Golconda, Sharada; Krishnaiah, Kurapati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Autologous bone marrow-derived stem cells (BMSCs) and platelet-rich plasma (PRP) separately were found to be effective in restoring ovarian function in infertile women. The present study aims to study the synergistic effect of bone marrow-derived aspirate concentrate (BMAC) and PRP in women diagnosed with poor ovarian response (POR) and premature ovarian failure (POF) undergoing in vitro fertilization (IVF). A total of 10 patients participated in the study. Eight patients were diagnosed with POR, while two patients had POF. Intraovarian BMAC-PRP injection was given to all the patients via the laparoscopic or transvaginal route. Group 1 before starting the IVF cycle, group 2-intracycle-post ovum pick-up and group 3-POF patients. Outcomes assessed include improvement in antral follicular count (AFC), Anti-Mullerian hormone (AMH), response to ovarian stimulation at subsequent IVF cycle and clinical pregnancy. In group I POR patients (n=4) post-instillation, an increase in AFC count was observed and subsequently, these patients underwent IVF, however, no clinical pregnancies were achieved. Group II POR patients (n=4), who received BMAC-PRP instillation intracycle post-OPU there was improvement in AFC and better response with more oocytes and embryos in the subsequent IVF cycle, leading to three pregnancies in this group. In group III-POF patients (n=2) who received BMAC-PRP instillation, one of them spontaneously conceived post 3 months of instillation. The synergistic application of BMAC-PRP was found to be effective in improving ovarian function in POR and POF patients.